یہودیت اور عیسائیت میں عبادت گاہ کاتصور اور احترام:اختصاصی مطالعہ: The Concept and Respect for the Temple (Place of worship) in Judaism and Christianity: Specific study - Talha Khursheed; Dr. Muhammad Shahid Habib; Dr. Mazhar Hussain Bhadroo (Al Manhal Research Journal, 2024)
It is difficult if not impossible to estimate the number of religions that have come to this earth from the creation of Adam until now, have deteriorated or disappeared and if a general estimate is made, this number will surely exceed hundreds. Although each of these religions has existed in a different time, place and status, one thing that all these religions have in common is the respect for their places of worship whether they are Semitic or non-Semitic. Although there are some religions such as Buddhism, etc. which are devoid of the concept of God but they also have a system of worship and respect their place of worship. Yes, it is a different matter that there has been and still is a difference in the status and nature of their concept of worship. The respect and reverence of the place of worship in the hearts of the followers of religions is not for anything else. In the religion of Islam, the place of worship has a separate status. The concept of the place of worship in religion is different from the rest. The place of worship of Muslims is called a mosque. Similarly, in other religions, the respect related to places of worship is the same as in Islam whether it is a church or a temple, everyone respects the place of worship. This article provides an analytical overview of the concept and respect for places of worship in Judaism and Christianity